IMPROVEMENT OF RECRUITMENT PROCESS FOR TRAINEES IN LINGKAR KALAYA NUSWANTARA COOPERATIVE (The Indonesian Journal of Business Administration, 2021)
Cooperatives have a general purpose, to improve their member’s welfare. Lingkar Kalaya Nuswantara is one of the cooperatives in Indonesia. The cooperation is established on 2018 but receive their formal recognition from the government in 2019 by acquiring their cooperative id. Lingkar Kalaya Nuswantara is based on Jakarta, Indonesia but they have a training center for their members in Lembang, West Java, Indonesua. They are backed by Indonesian Ministry of Manpower. They worked on services sector. With the improvement of Indonesia and Japan relationship and the declining number of productive workforces in Japan, it become an opportunity for Indonesian workforce to work abroad especially in Japan. For migrant worker Japan has their own policy called SSW (Specialized Skilled Worker). Lingkar Kalaya Nuswantara sees this as an opportunity and because their relationship with one of Japanese Cooperation, they want to be one of the organizations that will send worker to Japan. Their program called “dijepang”. They will give an orientation to their trainee and short course before they work abroad. To acquire the skilled worker of their own, Lingkar Kalaya Nuswantara need to recruit them. A proper recruitment process will help an organization to recruit the candidate that suit them. Also, with a proper recruitment process the organization can filter the candidate and eventually choose the best talent that apply to a position. A best talent will help the organization to gain competitive advantage. Lingkar Kalaya Nuswantara is a new cooperative, and they just launch the “dijepang program”, they already conduct a recruitment process trial, and they recruit ten trainees. But their recruitment process is unsustainable and unreliable if they want to recruit a large number of trainees, so their recruitment process still needs an improvement. This study aims to give the recommendation on the improvement of the recruitment process and also a competency dictionary as a basis of evaluating every candidate. This study uses a qualitative approach by doing an interview to several people that involved in the cooperative especially the program. After gathering the data and doing a theoretical study this study will provides the improvement of the recruitment process and also the core competency dictionary. The recommendation from this study will help the cooperative solve their problem regarding the recruitment process of “dijepang program”.Keywords: Recruitment, Competency, Recruitment Process, Core Competency, Competency Dictionary